Elusive groups of automorphisms of digraphs of small valency. (May 2015) - Giudici, Michael; Morgan, Luke; Potočnik, Primož; Verret, Gabriel
Abstract: A transitive permutation group is called elusive if it contains no semiregular element. We show that no group of automorphisms of a connected graph of valency at most four is elusive and determine all the elusive groups of automorphisms of connected digraphs of out-valency at most three.